Physical activity promotion in physiotherapy practice: a systematic scoping review of a decade of literature. Issue 2 (21st December 2016) - Lowe, Anna; Gee, Melanie; McLean, Sionnadh; Littlewood, Chris; Lindsay, Carolyn; Everett, Simon
Abstract : Background: The health benefits of physical activity (PA) have been extensively documented. Globally PA levels are low with only a small proportion of the population reaching recommended levels. Insufficient PA is seen as a major public health problem with high cost to society. Physiotherapists work with people to manage long-term conditions and are well placed to deliver individual interventions to increase PA. Despite this, little is known about the evidence that exists in this field. Methods: This scoping review comprises a comprehensive search of key databases using predetermined search terms. This is supplemented with a parallel search that incorporated novel social media strands. In line with current guidance, a robust screening process took place using agreed inclusion and exclusion criteria. Results: 31 studies met the inclusion criteria. The number of studies published annually increased over the decade. Ireland and USA yielded the largest number of publications with only 1 study from the UK. The target populations included physiotherapists and service users from a range of clinical populations. The studies were mainly quantitative and observational in design with a predominance of studies that scoped attitudes, perceptions, barriers and current practice. Conclusions: This reconnaissance has shown the state of the evidence to be sparse and disparate. However, the sharp rise in published work in recent years is encouraging. The predominance of scoping studies and the clear social, economic and political drivers for change in this area highlights a need for more pragmatic, interventional studies that can inform clinical practice.